Odpowiedzi

2010-02-18T17:22:53+01:00
Moja legenda: ^ - to jest "do kwadratu"
Działanie:
(2x-1)^/2 - (2x-3)(2x+3)/4 = 1+x /*4 ,czyli wszystko mnożysz razy 4 zeby ułamki się skróciły
2(2x-1)^-(2x-3)(2x+3)=4+4x
2(4x^-4x+1)-4x^-9=4+4x
8x^-8x+2-4x^-9=4+4x
8x^-8x-4x^-4x=4-2+9
4x^-12x=11
2010-02-18T17:24:48+01:00
(2x - 1)²/2 - (2x - 3)(2x + 3)/4 = 1 + x
2(2x - 1)² - (4x² - 9) = 4(1 + x)
2(4x² - 4x + 1) - 4x² + 9 = 4 + 4x
8x² - 8x + 2 - 4x² + 9 - 4 - 4x = 0
4x² - 12x + 7 = 0
Δ = 144 - 112
Δ = 32
√Δ = √32 = 4√2
x1 = (12 - 4√2)/2 = 6 - 2√2 = 2(3 - √2)
x2 = (12 + 4√2)/2 = 6 + 2√2 = 2(3 + √2)